2004
DOI: 10.1038/sj.onc.1207966
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of GATA3 in human breast tumors

Abstract: GATA3 is an essential transcription factor that was first identified as a regulator of immune cell function. In recent microarray analyses of human breast tumors, both normal breast luminal epithelium and estrogen receptor (ESR1)-positive tumors showed high expression of GATA3. We sequenced genomic DNA from 111 breast tumors and three breast-tumor-derived cell lines and identified somatic mutations of GATA3 in five tumors and the MCF-7 cell line. These mutations cluster in the vicinity of the highly conserved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
270
3
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 245 publications
(293 citation statements)
references
References 42 publications
(50 reference statements)
15
270
3
5
Order By: Relevance
“…The prevalence of GATA3 mutations in the current DCIS cohort is significantly higher than that reported in invasive breast cancer (4-22%) 4,5,30,31 and in DCIS. Recently, Abba et al 14 reported a GATA3 mutation rate of 7% in 30 pure high grade DCIS cases while Kim et al 15 observed GATA3 mutation in one low grade DCIS out of a cohort of in six DCIS lesions of various nuclear grades (16.7%).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The prevalence of GATA3 mutations in the current DCIS cohort is significantly higher than that reported in invasive breast cancer (4-22%) 4,5,30,31 and in DCIS. Recently, Abba et al 14 reported a GATA3 mutation rate of 7% in 30 pure high grade DCIS cases while Kim et al 15 observed GATA3 mutation in one low grade DCIS out of a cohort of in six DCIS lesions of various nuclear grades (16.7%).…”
Section: Discussioncontrasting
confidence: 67%
“…4,5,30,31 We therefore evaluated GATA3 mutation status in a further 91 pure DCIS cases using Sanger sequencing of exons 5 and 6 (as DNA was limited). Nonsynonymous or splice region mutations were identified in 21/91 cases (23%, Supplementary Table 1), for a final frequency of 30/111 cases (27%).…”
Section: Mutated Genes In Dcismentioning
confidence: 99%
“…Loss of GATA3 function is associated with increased tumorigenesis and was found to be enriched in non-BRCA1/BRCA2 familial breast cancers (Arnold et al, 2010). Somatic GATA3 mutations have also been detected in Luminal A and B subtypes suggesting that and it is thought that GATA3 may confer a generalized growth inhibitory phenotype across a number of different tumor types (Usary et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Defining the molecular and cellular basis of this process is essential for understanding mammary development and associated defects, including breast cancer. The fact that breast cancer stem cells share some characteristics with mammary stem cells (Al-Hajj et al, 2003;Visvader and Lindeman, 2008) and that mutations in a number of the genes associated with mammary development have also been implicated in breast cancer (Usary et al, 2004;Bogorad et al, 2008) suggests that studies on mammary development may help define the early events that precede breast tumourigenesis.…”
Section: Introductionmentioning
confidence: 99%